Mapping and characterization of quantitative trait loci for mesocotyl elongation in rice (Oryza sativa L.) - Lee, Hyun-Sook; Sasaki, Kazuhiro; Higashitani, Atsushi; Ahn, Sang-Nag; Sato, Tadashi (Springer, 2012)
Mesocotyl elongation is an important trait for seedling emergence in direct-seeding cultivation in rice. In this study, a backcross inbred line (BIL) population from a cross between Kasalath and Nipponbare was employed to map quantitative trait loci (QTLs) for mesocotyl elongation. A total of 5 QTLs for mesocotyl length were identified on chromosomes 1, 3, 7, 9, and 12 in 2 independent experiments. At all QTL, the Kasalath alleles contributed to an increase in mesocotyl length. Two QTLs (qMel-1 and qMel-3) on chromosomes 1 and 3 were consistently detected in both experiments. To fine map the QTLs, a cross was made between 2 chromosome segment substitution lines (CSSL-6 and CSSL-15), each harboring the Kasalath allele across the qMel-1 and qMel-3 regions, and an F-2:3 population was developed. A two-way ANOVA indicated that no epistatic interaction was detected between the 2 QTLs in the F-2 population (P = 0.31). Moreover, analysis of two F-3 near-isogenic lines (NILs) derived from the same cross, indicated that the 2 QTLs act additively in distinct or complementary pathways in controlling mesocotyl elongation. Substitution mapping indicated that the qMel-1 QTL was located between the 2 SSR markers RM5448 and RM5310, which are 3,799-kb apart, and that the qMel-3 QTL was located between the 2 SSR markers RM3513 and RM1238, which are 6,964-kb apart. To our knowledge, this is the first report to fine-map QTLs for mesocotyl elongation and to analyze their interaction